-6+9g=10g

Simple and best practice solution for -6+9g=10g equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6+9g=10g equation:


Simplifying
-6 + 9g = 10g

Solving
-6 + 9g = 10g

Solving for variable 'g'.

Move all terms containing g to the left, all other terms to the right.

Add '-10g' to each side of the equation.
-6 + 9g + -10g = 10g + -10g

Combine like terms: 9g + -10g = -1g
-6 + -1g = 10g + -10g

Combine like terms: 10g + -10g = 0
-6 + -1g = 0

Add '6' to each side of the equation.
-6 + 6 + -1g = 0 + 6

Combine like terms: -6 + 6 = 0
0 + -1g = 0 + 6
-1g = 0 + 6

Combine like terms: 0 + 6 = 6
-1g = 6

Divide each side by '-1'.
g = -6

Simplifying
g = -6

See similar equations:

| 49c^2-25d^6= | | (x+4)x(x-5)=-14 | | 3q-8=4q | | -4t=-8t-12 | | -3v=2-3v | | 20x-36*-20=-6 | | -15+7y=25+2y | | 15x=345 | | 5(n+3)-7=23 | | 15x=355 | | 12(x^2-15x+40)=0 | | -7-6=8 | | 13x+7(-3*-1)=-63 | | 2t-7= | | 10x+48=180 | | X+y=480 | | 2(2x-4)-2=2(x-5)+4 | | 3x+20=2x+11 | | 7t+5=5t+7 | | 7=b-4 | | -5n^2+3n+224=0 | | 2x+y=480 | | 13x=5x+48 | | 2y-4=10y+36 | | 4b-3=3b+9 | | 2(x^2+60x-200)=0 | | 14x+8=6x+12 | | 2x^5-32=0 | | 2(6x-4)=27 | | log(x+12)=3 | | 2x-[X+1]=5 | | 60=15d |

Equations solver categories